Antibacterial activity of Rosmarinus officinalis L. and Thymus vulgaris L. essential oils and their combination against food-borne pathogens and spoilage bacteria in ready-to-eat vegetables. Issue 24 (17th December 2019) - Iseppi, Ramona; Sabia, Carla; de Niederhäusern, Simona; Pellati, Federica; Benvenuti, Stefania; Tardugno, Roberta; Bondi, Moreno; Messi, Patrizia
Abstract: The antibacterial activity of Rosmarinus officinalis L. and Thymus vulgaris L. essential oils (EOs), and their combination against food-borne and spoilage bacteria ( Listeria monocytogenes, Salmonella enteritidis, Yersinia enterocolitica, Escherichia coli and Pseudomonas spp.) was determined. The EOs inhibitory effect was evaluated both in vitro by using the disk diffusion assay and the minimum inhibitory concentration (MIC) determination, and on food by using an artificially contaminated ready-to-eat (RTE) vegetables. The results showed that the lowest MIC values were obtained with R. officinalis and T. vulgaris EOs against E. coli (4 and 8 μL/mL, respectively). The incorporation of the EOs alone or their combination in RTE vegetables reduced the viable counts of all the tested strains. Lastly, in the on food study we simulated the worst hygienic conditions, obtaining results that can be considered a warranty of safety. Abstract :